Perbedaan Ukuran Kanul Suction Terhadap Perubahan Kadar Saturasi Oksigen Di Ruang ICU RSUD Dr. Moewardi Tahun 2015 - Yunita Kusuma Wardhani ((JKG) Jurnal Keperawatan Global, 2018)
Background: Patients treated at the ICU room one of them have an exhalation problem. Most of them needed a helping breath like a mechanical ventilator. Patients who needed a mechanical ventilator have a poor cough, so this secret will be a plaque in the lung cavity. A step to reduce plaque, therefore, doing suction care. There are many actions can be noticed to doing suction care is by choosing a cannula measure. This research works through to a distinguishment of cannula measure for change to titrate saturate oxygen on a rigged patient mechanical ventilator at spatial ICU RSUD Dr. Moewardi. Method: The type of this research is quasi-experimental with pre is and post's test control design's group. The Result: This observational result there is a cannula measure difference for change to titrate saturate oxygen on a rigged patient mechanical ventilator at ICU RSUD Dr. Moewardi Surakarta. kanul's measure 12F have greater influence appealed by kanul's measure 10F which is as big as 0.001, meanwhile, cannula measure 10F has to change as big as 0.029. Conclusion: The difference cannula measure suction having for change to titrate saturated oxygen.